EVALUATION OF GRA6 AS GENETIC MARKER FOR DETERMINING TOXOPLASMA GONDII GENOTYPE IN THE CEREBROSPINAL FLUID OF HIV/AIDS PATIENTS WITH TOXOPLASMIC ENCEPHALITIS - HARMINARTI, Nora; SARI , IKA Puspa; ARTAMA , Wayan Tunas; IMRAN, Darma; KURNIAWAN, Agnes (African Journal of Infectious Diseases (AJID), 2024)
Background: Toxoplasmic encephalitis is a severe manifestation of Toxoplasma gondii infection, with potentially fatal outcomes, particularly among immunocompromised patients. Clinical manifestation of this infection is associated with a specific genotype of T. gondii, requiring the use of genetic marker for genotype determination. Aims: This study critically evaluated the application of GRA6 gene as genetic marker for genotyping T. gondii in cerebrospinal fluid (CSF) samples from HIV/AIDS patients diagnosed with Toxoplasmic encephalitis. Methods: The study analyzed 69 CSF samples from HIV/AIDS patients with Toxoplasmic encephalitis. These samples tested positive for Toxoplasma IgG serology and SAG2 PCR, while GRA6 genotyping was conducted using PCR-sequencing methods. Results: The results showed that GRA6 had potential for genotyping in positive control settings from culture cells. However, there was limited effectiveness in CSF samples from Toxoplasmic encephalitis patients. Conclusion: GRA6 had been proven effective as a genetic marker for the identification of T. gondii genotype among HIV/AIDS patients with Toxoplasmic encephalitis. However, the evaluation of GRA6 showed more effectiveness in cultured cells compared to direct clinical samples, such as cerebrospinal fluid obtained from HIV/AIDS patients with Toxoplasmic encephalitis.